2021
DOI: 10.21037/atm-21-6234
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 attenuates the inflammation and oxidative stress induced by diabetic nephropathy through regulating the PI3K/AKT/FOXO3 pathway

Abstract: Background: Diabetic nephropathy (DN) is one of the most common microvascular complications in diabetes mellitus. Ginsenoside Rg1 (Rg1) is an important active ingredient extracted from Panax ginseng. This study aimed to investigate the role and molecular mechanism of Rg1 in DN model. Methods: The mesangial cell line HBZY-1 was induced by high glucose (HG; 30 mM D-glucose). HGinduced HBZY-1 cells were treated with Rg1 (2.5, 5, 10 μmol/L). Cell viability was measured by the MTT assay. Apoptosis was detected by H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
(55 reference statements)
1
26
1
Order By: Relevance
“… 21 The imbalance of oxidative status in renal tissues is manifested by elevated MDA levels, which is consistent with previous reports. 30–32 In our study, we found that DN rats accompanied by upregulation of NLRP3 inflammasome expression exhibited a significant oxidative stress state, such as elevated MDA and reduced antioxidant enzyme SOD, accompanied by altered renal tissues, consistent with previous studies, 32 considering the involvement of NLRP3 inflammasomes in the oxidative stress response in glycogenic renal tissues. In contrast, Sac treatment successfully down-regulated MDA expression by down-regulating inflammasome expression, blocking the renal oxidative stress response and reducing renal tissue damage.…”
Section: Discussionsupporting
confidence: 92%
“… 21 The imbalance of oxidative status in renal tissues is manifested by elevated MDA levels, which is consistent with previous reports. 30–32 In our study, we found that DN rats accompanied by upregulation of NLRP3 inflammasome expression exhibited a significant oxidative stress state, such as elevated MDA and reduced antioxidant enzyme SOD, accompanied by altered renal tissues, consistent with previous studies, 32 considering the involvement of NLRP3 inflammasomes in the oxidative stress response in glycogenic renal tissues. In contrast, Sac treatment successfully down-regulated MDA expression by down-regulating inflammasome expression, blocking the renal oxidative stress response and reducing renal tissue damage.…”
Section: Discussionsupporting
confidence: 92%
“…The antioxidative stress effect of 20( R )-Rg3 is related to the activation of the PI3K/AKT signaling pathway. Liu et al [ 97 ] found that ginsenoside Rg1 treatment alleviated high glucose-induced oxidative stress by decreasing ROS generation, MDA, and LDH accumulation and increasing the activities of SOD and GSH-Px. The molecular mechanism of Rg1 is considered related to the regulation of the PI3K/AKT/FOXO3 pathway.…”
Section: Roles Of Ginsenosides and Different Signaling Pathways In Th...mentioning
confidence: 99%
“…Rg1 mitigates inflammation and oxidative stress caused by diabetic nephropathy by mediating the PI3K/AKT/FOXO3 pathway. 33 Equally importantly, ginsenoside Rg1 ameliorates LPS-induced chronic kidney injury by reducing NOX2-mediated oxidative stress 34 and effectively alleviates aldosterone-induced oxidative stress and podocyte autophagy 35 and kidney injury. 36 As acknowledged, ferroptosis is extremely associated with enhanced lipid peroxidation and overproduction of ROS.…”
Section: Ginsenosidementioning
confidence: 99%
“…Previous research has documented that ginsenoside Rg1 could protect against kidney injury by attenuating oxidative stress 32 . Ginsenoside Rg1 mitigates inflammation and oxidative stress caused by diabetic nephropathy by mediating the PI3K/AKT/FOXO3 pathway 33 . Equally importantly, ginsenoside Rg1 ameliorates LPS‐induced chronic kidney injury by reducing NOX2‐mediated oxidative stress 34 and effectively alleviates aldosterone‐induced oxidative stress and podocyte autophagy 35 and kidney injury 36 .…”
Section: Introductionmentioning
confidence: 99%